Measuring Welfare Equality: Essential Factors Supporting Inclusive Economic Growth in West Nusa Tenggara Province 2021-2025 - Fatimah, Siti; Haryanto, Tri; Solihin, Achmad (Jurnal Ekonomi Kuantitatif Terapan, 2025)
Inclusive economic growth is a new paradigm in measuring the success of economic development in current era. The purpose of this study is to analyze and identify the essential factors that support inclusive economic growth in the regency / city of NTB Province for the next five years (2021-2025). This research uses the semi-averaging method in calculating data projections in 2024-2025. The data analysis technique used in this research is panel data regression. The findings of this study indicate that over the next five years (2021-2025) inclusive economic growth in NTB regency / city is predicted to be in the medium category. The findings of this study also show that a decrease in poverty levels, income inequality and unemployment rates are important factors that support inclusive economic growth in Regency / City in NTB Province in the next five years (2021-2025). Keywords: Inclusive Economic Growth, Poverty Rate, Income Inequality,  Unemployment Rate